SNODGRASS HYPOSPADIAS REPAIR AT AYUB TEACHING HOSPITAL: AN AUDIT OF COMPLICATIONS AND OUTCOMES - Shawana Asad; Fawad Ahmed Khan; Sher Ali; Khan, Hafizullah; Hina Rafaqat; Irfan Khattak (Journal of Ayub Medical College Abbottabad, 2023)
Background: There are many reported techniques for the repair of hypospadias, and new ones are being reported, which suggests that none is perfect. This study reports the anatomical success rate when using Snodgrass Technique. Methods: In this descriptive case series, 296 patients who fulfilled the inclusion criteria, by being treated by Snodgrass urethroplasty, were enrolled. The study was conducted at the Department of Surgery, Unit-C, MTI, Ayub Teaching Hospital Abbottabad between May 2008 and June 2021. Results: Mean age of the patients was 2.4±.8 years, 79.7% (n=236) had anterior (glanular, coronal, sub coronal) meatal location and 20.3 % (n=60) had middle urethral meatus (distal & mid-shaft). The mean operative time was 52 min. 5.1% of patients developed neo-meatal stenosis (n=15), 7.1% (n=21) patients develop a urethral-cutaneous fistula (compared to 5% in larger centers, 16% from smaller centers), 11.8% (n=35) developed wound infection, 2% (n=6) had complete disruption. Follow-up: The cosmetic appearance of the penis was excellent/good (shape of meatus was slit-like and vertically oriented) in 60.1% (n=178) patients, acceptable in 30.1% (n=89), and not acceptable in 9.8% (n=29). Conclusion: Snodgrass technique has a low complication rate, offers an acceptable cosmetic outcome and can be successfully applied to a wide range of defects from distal to mid-shaft hypospadias. Common complications include urethral-cutaneous fistula and meatal stenosis; both occur in a low and acceptable number of patients.